A culinária caiçara e a prática da hospitalidade nos restaurantes especializados em peixes e frutos do mar da Baixada Santista - SILVA, Luciana Marchetti da (2016)
seafood in Baixada Santista, State of São Paulo, Brazil. Using feedstock combination and local habits, the regional cuisine portrays historical experiences and cultural heritages. In this sense, its supply provides the interaction among people, contributing to the development of social ties, thus realizing the act of hospitality. The globalization and industrialization phenomena have modified the feeding habit of Brazilian population and the last decades of the twentieth century were marked by the standardization of food and the overconsumption of industrialized products to the detriment of the regional food with its cultural tradition. In the twenty first century and in an opposite scenario, subjects such as sustainability, appreciation of the regional cuisine and its ingredients and the use of organic and seasonal foods gained centrality in Brazilian gastronomy, inspiring different movements that have as a goal the recovery of the regional particularities. Following that trend, restaurants seek to offer hospitality services allied to the maintenance of the regional culture. From that context comes up the issue: which factors influence the Caiçara cuisine representativeness and the practice of hospitality in restaurants whose expertize are fish and seafood in Baixada Santista? This research is both exploratory and descriptive, being qualitative and quantitative at the same level. Besides the bibliographical research, data was collected using semistructured interviews with the restaurants’ managers; these managers answered a questionnaire based on Likert scale and a survey was also done about traditional dishes of Caiçara cuisine enclosed in the menus. Between March 28 and May 4, 2016, 44 restaurants’ managers specialized in fish and seafood answered the mentioned survey in São Vicente, Santos and Guarujá. It was used the method proposed by Bardin (2011) for the interview content analysis. Regarding to the statistical methodology, it was used the sign test for the median, the Spearman and Person correlation and the Cronbach’s alpha statistics. The following softwares were used: SPSS V 17, Minitab 16 and Excel Office 2010. It was demonstrated that the mistaken concept about Caiçara cuisine and the limited knowledge about hospitality, on the part of restaurants’ managers, are the main element that influence in this cuisine representativeness and in the practice of hospitality. About caiçara cuisine, most managers think is the cooking of the Brazilian coast and relates to any dish prepared with fish and seafood, citing, including dishes of other nationalities, such as paella, codfish portuguese, octopus spanish, etc. With reference to the ingredients, only cited fish, did not mention the banana, cassava flour, palmetto, taioba, jabuticaba, and many others featuring caiçara cuisine. It was veryfied that the following Caiçara dishes are the major offer: shellfish to vinaigrette, Shrimp to Paulista, grilled fish fillet, fried calamari, fried shrimp, toasted manioc flour, fish mush, banana manioc flour, fried cassava and roasted mullet. Concerning to the hospitality practices adopted, it was veryfied that the managers was worried about the following ritual: receive, accommodate and feed the guests. However, they forget the entertainment as part of the hospitality, as well as the ambiance, hygiene, infrastructure and the cultural aspects of the region.